AGE-DEPENDENT INHALATION DOSE DUE TO EXPOSURE OF SHORT LIVED PROGENY OF RADON AND THORON FOR DIFFERENT AGE GROUPS IN JAMMU & KASHMIR, HIMALAYAS. Issue 4 (16th May 2018) - Sharma, Sumit; Kumar, Ajay; Mehra, Rohit
Abstract: Dosimetric approach is used in this study for the assessment of doses due to inhalation of short lived radon/thoron progeny to the inhabitants of Udhampur district of Jammu & Kashmir. This paper also presents the activity concentrations and unattached fraction of radon and thoron progeny. The observed annual concentration of attached and unattached 222 Rn and 220 Rn progeny has been found to vary from 8 to 32 and 0.09 to 14 Bq/m 3, 0.75 to 3.16 and 0.01 to 1.13 Bq/m 3, respectively. The inhalation doses from radon progeny to different body organs of different age groups have been calculated by using the age dependent biokinetic model. The attachment rate of 222 Rn and indoor aerosol concentration of 222 Rn and 220 Rn have been estimated and their relation between them has also been studied. The dose conversion factor for mouth and nasal breathing to different exposure conditions has been obtained from Porstendorfer model.